Numerical algorithm for solving parabolic identification problem with mixed boundary condition - Charyyar Ashyralyyev; Tazegul Ashyralyyeva (E-Journal of Analysis and Applied Mathematics)
A source identification problem for a parabolic equation with mixed boundary condition is studied. Stability estimates for the solution of identification problem with mixed boundary conditions are obtained. Numerical algorithm for solving this inverse problem are proposed. Stability estimates for difference schemes are established. The numerical result in test example is presented.